Research Note on Experiences and Attitudes Going Forward with and Beyond Omicron (July) - Crothers, C (School of Social Sciences, Auckland University of Technology, 2022)
The attitudinal base of support for the current Covid strategy in NZ is assessed using current and recent survey data – covering attitudes and reports in relation to switching to the traffic light system, vaccination, border-opening, Covid-management issues and the various feelings and views in coping with Omicron. Evidence is compiled, too, on attitudes towards any resetting of New Zealand’s Covid-19 regime and possible pivots to alternatives. As NZ develops its way of dealing with the Omicron variant, the attitudinal and behavioural concomitants can be traced based on longitudinal surveys.
Keywords: New Zealand; Auckland; Covid-19; Omicron; Lockdowns; Border; Mask-wearing; Social distancing; Stress; Economic difficulties; Surveys; Survey series